Influence of environmental variables and anthropogenic activities on soda-saline lakes chemistry in northern Tanzania: A remote sensing and GIS approach - Azaria Stephano Lameck; Brian Rotich; Abdalrahman Ahmed; Harison K. Kipkulei; Peto Akos; Emil Boros (Heliyon)
This study employed Remote Sensing and Geographical Information Systems to explore the influence of environmental factors and human-induced land use/land cover changes on the chemistry of soda-saline lakes in Northern Tanzania. Satellite-based rainfall data were sourced from the Climate Hazards Group Infrared Precipitation with Station (CHIRPS) datasets, and temperature data were obtained from MERRA-2. Monthly precipitation, temperature, and drought conditions in lake watersheds were analyzed from 1981 to 2022, while land use and land cover changes were assessed for 2000, 2014, and 2023. Soil types were acquired from the FAO Digital Soil Map of the World, while geological characteristics were sourced from the US Geological Survey database. The findings revealed that the region's climate is ideal for enhancing evapotranspiration, leading to mineral precipitation, and altering the chemistry of soda-saline lakes. The Standardized Precipitation Evapotranspiration Index revealed increased drought events in the lake basins since 1987, with prolonged drought occurrence between 2000 and 2017. The results also showed that the region is characterized by a variety of soil types, including ferric acrisols, chromic cambisols, calcic cambisols, entisols, inceptisols, eutric fluvisols, distric nitisols, humic nitisols, mollic andosols, ochric andosols, and pellic vertisols. Furthermore, the region is distinguished by diverse geological processes, from Precambrian-Cambrian to tertiary intrusive, triggered by volcanic and tectonic activity. Land use/land cover changes results indicated dynamics in the various classes with an overall decrease in areas under water bodies (−39.80 %), forests (−22.57 %) and bareland (−36.18) while agricultural land (111.01 %) built-up areas (434.72 %), shrubs and grasses (72.77 %) increased in area coverage over the 23 years study period (2000–2023). This study underscores the complex interplay between environmental variables and human activities in shaping the chemistry of soda-saline lakes.